Effects of estradiol on bone in men undergoing androgen deprivation therapy: a randomized placebo-controlled trial. Issue 2 (27th June 2022) - Russell, Nicholas; Ghasem-Zadeh, Ali; Hoermann, Rudolf; Cheung, Ada S; Zajac, Jeffrey D; Shore-Lorenti, Cat; Ebeling, Peter R; Handelsman, David J; Grossmann, Mathis
Abstract: Objective: In men, many effects of testosterone (T) on the skeleton are thought to be mediated by estradiol (E2), but trial evidence is largely lacking. This study aimed to determine the effects of E2 on bone health in men in the absence of endogenous T. Design: This study is a 6-month randomized, placebo-controlled trial with the hypothesis that E2 would slow the decline of volumetric bone mineral density (vBMD) and bone microstructure, maintain areal bone mineral density (aBMD), and reduce bone remodelling. Methods: 78 participants receiving androgen deprivation therapy for prostate cancer were randomized to 0.9 mg of 0.1% E2 gel daily or matched placebo. The outcome measures were vBMD and microarchitecture at the distal tibia and distal radius by high-resolution peripheral quantitative CT, aBMD at the spine and hip by dual-energy x-ray absorptiometry, and serum bone remodelling markers. Results: For the primary endpoint, total vBMD at the distal tibia, there was no significant difference between groups, mean adjusted difference (MAD) 2.0 mgHA/cm 3 (95% CI: −0.8 to 4.8), P  = 0.17. Cortical vBMD at the distal radius increased in the E2 group relative to placebo, MAD 14.8 mgHA/cm 3 (95% CI: 4.5 to 25.0), P  = 0.005. Relative to placebo, E2 increased estimated failure load at tibia, MAD 250 N (95% CI: 36 to 465), P  = 0.02, and radius, MAD 193 N (95% CI: 65 to 320), P  = 0.003. Relative to placebo, E2 increased aBMD at the lumbar spine, MAD 0.02 g/cm 2 (95% CI: 0.01 to 0.03), P  = 0.01, and ultra-distal radius, MAD 0.01 g/cm 2 (95% CI: 0.00 to 0.02), P  = 0.01, and reduced serum bone remodelling markers. Conclusion: Relative to placebo, E2 treatment increases some measures of bone density and bone strength in men and reduces bone remodelling, effects that occur in the absence of endogenous T.